Tourist gaze upon a slum tourism destination: A case study of Dharavi, India. (September 2022) - Shang, Yuanyuan; Li, Fangxuan (Sam); Ma, Jianan
Abstract: This study applied the concept of the 'tourist gaze' to investigate tourists' perceptions of slum tourism in Asia's largest slum community, Dharavi, India, using 458 reviews collected from the travel comparison website, TripAdvisor. In this study the application of the tourist gaze concept has been extended by exploring the functions of tourist gaze in the context of slum tourism. It was found that tourists tended to gaze upon the local environment (natural, socio-cultural, and economic environment) and residents (residents' spirit, residents' life, and local tour guides) during their visits. The study further demonstrated that tourists' perceptions of slums and their attitudes towards life, changed after gazing upon slum destinations. Theoretically, a model of the slum tourism travel experience has been developed, based on the findings of this study. Practically, this study offers suggestions for slum tourism operators, to better improve slum tourism from the perspective of tourists.